The effects of smart phone video analysis on focus of attention and performance in practice and competition - Yeoman, B.; Birch, P. D. J.; Runswick, O. R. (Psychology of Sport and Exercise, 2020)
Objectives: Research has consistently found that focus of attention (FOA) affects motor learning and performance. However, much of the previous work has used artificially manipulated FOA of novice participants performing laboratory tasks. There is a paucity of work that has tested transfer to more complex competition environments. We aimed to investigate the effects of smart phone video analysis, which commonly occurs in natural practice settings in golf, on skilled player`s FOA and performance in both practice and competition.